مکی سورتوں میں مدنی اور مدنی سورتوں میں مکی آیات کا ورود؛ ایک تحقیقی جائزہ : The arrival of Macan Verses in Madani Surahs and Madani verses in Macan Surahs: A research review - Majeed, Maria; Noman Majeed, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2022)
The Holy Quran has been compiled in the order of detention; that is, the Holy Prophet himself gave instructions to the Companions about which verse to place and where he completed the Quran in the same order. He included Madani verses in some Macan Surahs, which may be due to the completion of subjects or the merging of similar verses and the continuation of the Quranic verse on which the commentators have different views. Some verses were revealed in Makkah after the Hijrah, but they are present in the Madani Surah according to the present order of detention. Similarly, the verses revealed during the journey, which were revealed in areas far from Madinah, the place of Mina and Arafat, and the journey to Meraj, are the verses of Mecca, even though they were revealed after the migration. The verses that were revealed during the migration were also included in the Macan Surahs and after the migration, you traveled hundreds of miles away from Madinah and the verses that were revealed at these places were Madani or Macan. If they were Madani, then why were they kept in Macan Surahs. Why was this done and what are the reasons for it? Is it not such an arrangement to invalidate the inspired Word? Was it a different order than the inspired one? Is it not possible to take these verses from the surahs in which these verses were revealed or to place them in other surahs, to spoil the connection of the previous surahs, or to leave their subjects incomplete? The article under discussion will discuss the topics, discussions, introduction of the verses, details, and reasons for placing the verses in their place in the Macan Surahs and the order and contextual context of these verses. An analytical study of the reasons for separation will be presented.